Effect of Hydroxyapatite on Surface Roughness of Zirconomer, and Conventional and Resin-Modified Glass Ionomers - Farahnaz Sharafeddin; Somaye Bahrani (Tehran University of Medical Sciences, 2021)
Objectives: Glass ionomer cements (GICs) are among the most popular dental restorative materials, but their use is limited due to their clinical disadvantages. Many efforts have been made to improve the properties of these materials by adding various fillers. Incorporation of hydroxyapatite (HA) into the GICs is considered to improve the physical properties of restorations, and may prevent treatment failure. This study aimed to evaluate the surface roughness (Ra) of a conventional glass ionomer cement (CGIC), a resin-modified glass ionomer (RMGI) and a Zirconomer with and without micro-hydroxyapatite (µHA). Materials and Methods: This experimental study was conducted on 6 groups (n=10) including CGIC, CGIC + µHA, RMGI, RMGI + µHA, Zirconomer, and Zirconomer + µHA. A total of 60 disc-shaped samples (6 mm × 2 mm) were prepared in plastic molds and were stored in distilled water for 24 h. After polishing of the specimens, their Ra was measured by a profilometer in micrometers (µm). The data were analyzed using two and one-way ANOVA, Tukey's HSD test, and independent t-test. Results: Incorporation of µHA resulted in statistically significant differences in Ra between the study groups (P<0.05). Following the incorporation of µHA, the Ra significantly decreased in CGIC (P=0.013) and Zirconomer (P=0.003). However, addition of µHA to RMGI resulted in a significant increase in its Ra (P<0.001). Conclusion: Addition of µHA decreased the Ra of Zirconomer and CGIC, and increased the surface roughness of RMGI samples.